If it's not what You are looking for type in the equation solver your own equation and let us solve it.
d in (-oo:+oo)
6*(2-d) = 42 // - 42
6*(2-d)-42 = 0
6*(2-d)-42 = 0
-6*d-30 = 0
-6*d-30 = 0
-6*d-30 = 0 // + 30
-6*d = 30 // : -6
d = 30/(-6)
d = -5
d = -5
| 4(6-4m)=8 | | 3(-2a-10)=-60 | | 4(10+7b)=-212 | | 7(1t+6)=14 | | 6(10+2x)=180 | | 2(1x+3)=8 | | 7(3-4x)-5(2x+8)=0 | | 4(6m+3)=-276 | | 6(4+7d)=192 | | 5(2a+8)=40 | | 3(-1a-1)=-33 | | 6(-7b-1)=288 | | 5(2x-3)-3(x-2)=0 | | 2(7k+2)=-52 | | 7(9+6a)=357 | | 6(-3x+2)=-78 | | 2(9+5w)=138 | | 2(2-5b)=104 | | 3(5b+1)=18 | | 6(-1m+5)=-36 | | 4(4+2t)=80 | | 2(-1x-7)=-28 | | (5x+3)-(4x-9)=0 | | 7(2-5t)=14 | | 6(4+3m)=150 | | 6(-5-3m)=42 | | 6(2+k)=66 | | 6(3t+5)=246 | | 3(2a-9)=3 | | 2(-6m+9)=126 | | 2(5k+7)=74 | | 6(9-2n)=30 |